Pengaruh Kewajiban Kepemilikan NPWP, Pemeriksaan Pajak Dan Penagihan Pajak Terhadap Penerimaan Pajak Pada Kantor Pelayanan Pajak Pratama Bangkinang - Masril Masril (Economics, Business and Management Science Journal, 2021)
The purpose of this study was to determine whether there is an effect of NPWP ownership obligations on tax receipts at the Bangkinang Pratama Tax Service Office, to find out whether there is an effect of tax audits on tax receipts at the Bangkinang Pratama Tax Service Office, to determine whether there is an effect of tax collection on tax receipts at the Pratama Tax Service Office. Bangkinan, and to find out whether the NPWP ownership obligation, tax audit and tax collection have a simultaneous effect on tax revenues at the Bangkinang Primary Service Office.